Short-Run Relationships Between Indonesia’s Capital Market And BRICS Countries Using Granger Causality - Makmur Sianipar; Yohanes Indrayono; Hendro Sasongko (International Journal of Science and Environment (IJSE), 2025)
This study investigates the short-term causal relationships between Indonesia’s capital market and the stock markets of BRICS countries, Brazil, Russia, India, China, and South Africa, using the Granger Causality Test on daily data from June 2023 to May 2025. Following Indonesia’s formal membership in BRICS in January 2025, understanding these financial linkages becomes increasingly vital for portfolio diversification, risk management, and macroeconomic policy. The analysis reveals significant short-term causal interactions, particularly between the Jakarta Stock Exchange (JSX) and markets such as FTSEJSE (South Africa), BOVESPA (Brazil), MOEX (Russia), and SHANGHAI (China). South Africa emerges as a central transmitter of volatility, while Indonesia demonstrates both influence and sensitivity to BRICS markets. The findings highlight asymmetric integration within BRICS, indicating that while some markets exert predictive influence, others remain relatively independent in the short term. This research contributes to the literature by focusing on Indonesia’s strategic role post-membership and offering practical insights for investors and policymakers. Recommendations include enhancing real-time cross-country market surveillance and further research incorporating macroeconomic variables and nonlinear models to assess long-term integration. The study underlines the growing interdependence among emerging markets in an era of intensified globalization.